2019
DOI: 10.1186/s12864-019-5799-6
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-guided regulation of heat stress response in wheat

Abstract: Background: With rising global temperature, understanding plants' adaptation to heat stress has implications in plant breeding. MicroRNAs (miRNAs) are small, non-coding, regulatory RNAs guiding gene expression at the posttranscriptional level. In this study, small RNAs and the degradome (parallel analysis of RNA ends) of leaf tissues collected from control and heat-stressed wheat plants immediately at the end of the stress period and 1 and 4 days later were analysed. Results: Sequencing of 24 small RNA librari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(57 citation statements)
references
References 93 publications
2
55
0
Order By: Relevance
“…In eukaryotic cells, miRNAs coding genes are transcribed to generate primary miRNAs (pri-miRNAs), which are then cleaved and processed into mature miRNAs under the action of DICER-LIKE proteins (DCLs). In Arabidopsis, ARGONAUTE (AGO) family proteins such as AGO1 then bind the nascent mature miRNAs and guide the target-specific post-transcriptional gene silencing (PTGS) [97]. Unlike microRNA, short/small interfering RNAs (siRNAs) are generated from long linear double-stranded RNAs with 20-24 nt length and are transcribed by RNA polymerase IV (RNAPIV) from transposons and repetitive regions.…”
Section: Non-coding Rnasmentioning
confidence: 99%
See 1 more Smart Citation
“…In eukaryotic cells, miRNAs coding genes are transcribed to generate primary miRNAs (pri-miRNAs), which are then cleaved and processed into mature miRNAs under the action of DICER-LIKE proteins (DCLs). In Arabidopsis, ARGONAUTE (AGO) family proteins such as AGO1 then bind the nascent mature miRNAs and guide the target-specific post-transcriptional gene silencing (PTGS) [97]. Unlike microRNA, short/small interfering RNAs (siRNAs) are generated from long linear double-stranded RNAs with 20-24 nt length and are transcribed by RNA polymerase IV (RNAPIV) from transposons and repetitive regions.…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…Increasing evidence from Arabidopsis studies revealed that ncRNAs such as siRNAs and lncRNAs regulate plant stress-responsive gene expression through multiple epigenetic mechanisms, including DNA methylation, histone modification and genome topology changes [97]. For instance, siRNAs and lncRNAs both participate into the DNA de novo cytosine methylation via the RNA-directed DNA methylation (RdDM) pathway in Arabidopsis [105].…”
Section: Non-coding Rnasmentioning
confidence: 99%
“…The identified miRNA families and their diverse expression patterns at different stages implicated the complexity of miRNAs involved in the regulation of the response of anthers to heat stress. Usually, the miRNAs with high abundance are considered the dominant and functional products that respond to stresses, such as HT [28,29]. In our study, seven miRNA families (miR2949, miR167, and miR160 at the SCP stage; miR156 and miR172 at the MP stage; miR156 at the MRP stage; and miR393 and miR3476 at the PM stage) with expression abundance of more than 10% of the total expression abundance served as the main regulators that respond to HT stress with positive or negative regulation patterns (Figure 4a).…”
Section: Various Mirna Families Responding To Ht Stress At Differentmentioning
confidence: 99%
“…The miRNAs within the same family have a similar function attributable to their conserved sequence and structural configuration [6,23]. High-and low-abundance miRNAs may play major and minor regulatory roles, respectively [28,29]. The coordinated regulation of these two types of abundance of miRNAs ultimately leads to the regulation of heat stress response [28].…”
Section: The Expression Of High-and Low-abundance Mirnas Changes Divementioning
confidence: 99%
“…Thus, improving the adaptability to high temperature has become a new focus in the process of crop molecular breeding. Plant has developed elaborate regulatory mechanisms at morphological, physiological and molecular levels to cope with heat stress [34,35], and many studies have paid more attention on gene expression and its roles in response to abiotic stresses [36][37][38][39]. MiRNAs are a group of non-coding sRNAs that play essential roles in plant growth, development, and stress responses [20-23, 40, 41].…”
Section: Discussionmentioning
confidence: 99%